A survey of corporation bankruptcy models. - Lim, Hup Liang. (2008)
Our study discusses the development of the fixed covariates corporation bankruptcy models. In addition to examining traditional bankruptcy prediction models using MDA and logit analysis, we examined models not discussed in previous studies, including the parametric logistic model, split population model and Aalen’s additive hazard model.